2001
DOI: 10.1002/cne.1174
|View full text |Cite
|
Sign up to set email alerts
|

Structure and projections of white matter neurons in the postnatal rat visual cortex

Abstract: Transient contributions of subplate neurons to the initial development of the cortex are well-characterized, yet little data are available on a subpopulation of subplate neurons that persist in the white matter (WM) of the cerebral cortex across development. To characterize the WM neurons, differential interference contrast and Nomarski optics were used to visualize individual cells in the WM in slices of rat visual cortex at postnatal ages 9-23. Soma-dendritic morphology and local axonal projection patterns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
85
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 118 publications
12
85
0
Order By: Relevance
“…Thus, the fluorescently labeled population comprised two cell groups, i.e., cells with dendrites and axons extending beyond the white matter boundaries with preferential arborization in lower cortical layers, but also in the hippocampus and striatum (type 1), and smaller cells located in the lower third of the corpus callosum with processes confined by and large to the white matter (type 2). WMICs with axons projecting to the cortex were described previously (Meyer et al, 1991;Clancy et al, 2001;Tomioka and Rockland, 2007). Most EGFP-positive WMICs had comparably small axonal arbors and do not meet the criteria of long-range GABAergic projection neurons with an axonal arbor extending Ͼ1.5 mm into the cortex (Tomioka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the fluorescently labeled population comprised two cell groups, i.e., cells with dendrites and axons extending beyond the white matter boundaries with preferential arborization in lower cortical layers, but also in the hippocampus and striatum (type 1), and smaller cells located in the lower third of the corpus callosum with processes confined by and large to the white matter (type 2). WMICs with axons projecting to the cortex were described previously (Meyer et al, 1991;Clancy et al, 2001;Tomioka and Rockland, 2007). Most EGFP-positive WMICs had comparably small axonal arbors and do not meet the criteria of long-range GABAergic projection neurons with an axonal arbor extending Ͼ1.5 mm into the cortex (Tomioka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Basic morphological features of WMICs were indicative of a neuronal phenotype (Neuburger, 1922;Lund et al, 1975;Kostovic and Rakic, 1980;Chun and Shatz, 1989;Muller, 1994;Shering and Lowenstein, 1994;Eastwood and Harrison, 2005;Friedlander and Torres-Reveron, 2009;Loup et al, 2009), a notion that was also supported by electron microscopy data (Valverde and Facal-Valverde, 1988). While there is ample information about the immunohistochemical signature of WMICs, such as the expression of GABA and specific GABAergic interneuron markers (Innis et al, 1979;Adrian et al, 1983;Schmechel et al, 1984;Shults et al, 1984;Somogyi et al, 1984;Chan-Palay et al, 1985;Sandell, 1986;Yan et al, 1996;Bayraktar et al, 1997;Tao et al, 1999;Suárez-Solá et al, 2009), only a few studies focused on electrophysiological properties of WMICs (Clancy et al, 2001;Torres-Reveron and Friedlander, 2007;Friedlander and Torres-Reveron, 2009). The main hindrance for the identification of WMICs in acute slices is their scarcity.…”
Section: Introductionmentioning
confidence: 92%
“…12,13 They also differ in their connectivity, with superficial IWMNs forming more extensive connections with neurons in the overlying grey matter. 26 It may also be relevant that superficial IWMNs lie embedded within the corticocortical association fibres (or U-fibres), which run in the white matter immediately below layer VI, whereas, at least in the rodent, callosal fibres travel in the middle portion and corticofugal axons predominate in the deep white matter. [63][64][65] Any of these differences might explain the apparent selective involvement of superficial compared to deep IWMNs in schizophrenia.…”
Section: Methodologic Issuesmentioning
confidence: 99%
“…Firstly, the nature of IWMN alterations in schizophrenia is not clear; for example, Akbarian et al 16,17,19 found a redistribution of IWMNs with an increased density in the deep white matter, whereas Anderson et al 18 reported essentially the opposite pattern, with increased IWMN density in the superficial white matter. Secondly, the dendrites and axons of some adult IWMNs project into the neocortex, thalamus or hippocampus, [23][24][25][26] suggesting that they participate in neural circuits throughout life. This raises the possibility that any involvement of IWMNs in schizophrenia might arise from, and impact upon, events that occur long after the end of corticogenesis.…”
mentioning
confidence: 99%
“…Initial studies (Sugita, 1917) had already demonstrated that the rodent subplate is not really a transient structure, but a well defined layer (VIb or VII) which persists as a part of the 'traditional' cortex throughout the rodent lifespan. In recent years, the rodent subplate ⁄ layer VII has been increasingly recognized as a 'special case' probably characteristic for this specific group of mammals and with significantly different developmental history and postnatal roles in comparison with primates and humans (Reep & Goodwin, 1988;Reep, 2000;Valverde et al 1989Valverde et al , 1995Robertson et al 2000;Clancy & Cauller, 1999;Clancy et al 2001Clancy et al , 2009Arias et al 2002;Tomioka et al 2005).…”
Section: Lessons From History -New Trends In Subplate Researchmentioning
confidence: 99%